2014
DOI: 10.1038/ncomms4866
|View full text |Cite|
|
Sign up to set email alerts
|

Parallel T-cell cloning and deep sequencing of human MAIT cells reveal stable oligoclonal TCRβ repertoire

Abstract: Mucosal-associated invariant T (MAIT) cells are abundant in humans and recognize conserved bacterial antigens derived from riboflavin precursors, presented by the nonpolymorphic MHC class I-like molecule MR1. Here we show that human MAIT cells are remarkably oligoclonal in both the blood and liver, display high inter-individual homology and exhibit a restricted length CDR3b domain of the TCRVb chain. We extend this analysis to a second sub-population of MAIT cells expressing a semi-invariant TCR conserved betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
347
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 278 publications
(401 citation statements)
references
References 53 publications
41
347
2
Order By: Relevance
“…Most MAIT cell TCRs comprise a semi‐invariant TCR‐ α chain – usually TRAV1‐2‐TRAJ33 (V α 7.2 − J α 33 in humans, V α 19 − J α 33 in mice),90 although in humans some MAIT cells also use TRAV1‐2‐TRAJ12 or TRAV1‐2‐TRAJ2022) – predominantly associated with the β ‐chains TRBV20 (V β 2) or TRBV6 (V β 13) in humans1 and TRBV19 (V β 6) or TRBV13 (V β 8) in mice 1, 22, 23. These preferential TCR rearrangements arise partly through a process of ‘convergent recombination’91 whereby much of the antigen specificity of MAIT cells is essentially germline‐encoded.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most MAIT cell TCRs comprise a semi‐invariant TCR‐ α chain – usually TRAV1‐2‐TRAJ33 (V α 7.2 − J α 33 in humans, V α 19 − J α 33 in mice),90 although in humans some MAIT cells also use TRAV1‐2‐TRAJ12 or TRAV1‐2‐TRAJ2022) – predominantly associated with the β ‐chains TRBV20 (V β 2) or TRBV6 (V β 13) in humans1 and TRBV19 (V β 6) or TRBV13 (V β 8) in mice 1, 22, 23. These preferential TCR rearrangements arise partly through a process of ‘convergent recombination’91 whereby much of the antigen specificity of MAIT cells is essentially germline‐encoded.…”
Section: Introductionmentioning
confidence: 99%
“…MAIT cells share some similarities with invariant natural killer T (iNKT) cells, which are implicated in many autoimmune conditions,18, 19 including expression of a semi‐invariant TCR, restriction by non‐classical MHC molecules, and expression of the transcription factor promyelocytic leukaemia zinc finger protein (PLZF)20 although many differences exist, notably the nature of the ligands and the restriction molecule. Other significant features are the remarkable abundance of MAIT cells, which comprise approximately 5% of T cells in peripheral blood11, 17 and 20–40% of liver T cells in humans,15, 21 and their wide tissue distribution in blood, mucosal tissues, liver and joints 15, 19, 22, 23, 24, 25. A peculiarity of MAIT cell biology is that although MR1 expression is ubiquitous,3, 26 it is normally found only at very low levels on the cell surface 26, 27, 28.…”
Section: Introductionmentioning
confidence: 99%
“…As with CB MAIT cells, circulating adult MAIT cells co-cultured with bacteria infected cells (commensal and pathogenic E. coli strains) secreted IFNg, IL-17, and TNFa [61]. Following exposure to E. coli fed APCs, Lepour et al [44] have also reported increases in Th0, Th1 and Th2 cytokines from both Ja33 and Ja12 expressing MAIT cells. Production of Th1 and Th17 related cytokines is not confined to circulating MAIT cells.…”
Section: Cytokine and Chemokine Expression By Mait Cellsmentioning
confidence: 96%
“…In humans the invariant TCR consists of a canonical Va7.2 (TRAV 1-2 genes) chain joined to Ja33 (TRAJ33 gene) which is paired to a limited array of TCRb chains (Vb2, Vb13, or Vb22). Very recently it has been reported that alternative nonJa33 junctional genes can also be used (including Ja20 and Ja12), and that in combination with this a higher number of b chains can be present [43,44]. In mice the MAIT TCR is composed of Va19 joined to Ja33, and paired with Vb6 or Vb8 (TRBV19 or TRBV13 respectively).…”
Section: Characteristics Of Mait Cellsmentioning
confidence: 99%
See 1 more Smart Citation